Efficacy of Ceftaroline Fosamil for Bacteremia Associated With Community-Acquired Bacterial Pneumonia. Issue 1 (February 2014) - Jandourek, Alena; Smith, Alexander; Llorens, Lily; Thye, Dirk A.; Eckburg, Paul B.; Friedland, H. David
Abstract: Objectives: Few publications of prospective studies have described patient outcomes in community-acquired bacterial pneumonia (CABP)-associated bacteremia. Our objective, in performing this subgroup analysis, was to assess outcomes in subjects with CABP-associated bacteremia in 2 randomized, double-blind clinical studies comparing treatment with ceftaroline fosamil versus ceftriaxone.Methods: Our analysis summarizes baseline subject demographics, distribution of baseline pathogens isolated from blood cultures, clinical response rates at Day 4, and clinical cure rates at end of therapy and test of cure (8 to 15 days after end of therapy) in subjects with bacteremic CABP in the ceFtarOline Community-acquired pneUmonia trial vS ceftriaxone in hospitalized patients (FOCUS) studies.Results: In the FOCUS studies, 23 of 614 patients in the ceftaroline fosamil-treated group and 22 of 614 patients in the ceftriaxone-treated group had CABP-associated bacteremia. Baseline demographics were similar between groups. Streptococcus pneumoniae was the most common baseline bloodstream isolate. For subjects with CABP-associated bacteremia, clinical response/cure rates were similar at Day 4 (60.9% vs 59.1%), end of therapy (69.6% vs 72.7%), and test of cure (69.6% vs 68.2%) for ceftaroline fosamil and ceftriaxone, respectively.Conclusions: In subjects with CABP-associated bacteremia, ceftaroline fosamil demonstrated similar clinical outcomes at Day 4, end of therapy, and test of cure compared with ceftriaxone.